Hi i'm having problem finding inverse of this exponential equation. f(x)=4-2^(-x+1) f(y)=4-2^(-y+1) solve for y: x=4-2^-y+1 x= 4- (1/2^(-y+1)) What do i do next?
Follow Math Help Forum on Facebook and Google+
Originally Posted by Anemori Hi i'm having problem finding inverse of this exponential equation. f(x)=4-2^(-x+1) f(y)=4-2^(-y+1) solve for y: x=4-2^-y+1 x= 4- (1/2^(-y+1)) What do i do next?
Originally Posted by Anemori Hi i'm having problem finding inverse of this exponential equation. f(x)=4-2^(-x+1) f(y)=4-2^(-y+1) solve for y: x=4-2^-y+1 x= 4- (1/2^(-y+1)) What do i do next? An equivalent solution to the one posted above: If you think about it you should see that in general, , for suitable choice of b.
View Tag Cloud